Resistance in single-walled carbon nanotube networks formed on gold nanoparticle templates - Chalao Wongsaeng (2018)
The temperature dependence features of a typical intrinsic semiconductor resistance were used to study the resistances in single-walled carbon nanotube (SWNT) networks formed on gold nanoparticle (AuNP) templates, using the resistance-temperature relations in the temperature range from 440 to 570 K. The SWNTs were synthesized using the chemical vapour deposition method, with ethanol as a carbon source and cobalt particles as the catalyst. The synthesis was performed at 1073 K, for a duration of 60 min. It was found that the negative temperature coefficients and the energy gaps, which indicated the degree of semiconductor behaviour, increased with increasing sample starting resistance. However, at the same sample starting resistance, the degree of semiconductor behaviour increased with increasing AuNP number density, resulted from the change in the effective diameter of the semiconducting SWNTs of the sample, which occurred because of the effects of the AuNP number density. © 2013 IOP Publishing Ltd.